Patient-reported depression measures in cancer: a meta-review. (July 2015) - Wakefield, Claire E; Butow, Phyllis N; Aaronson, Neil A; Hack, Thomas F; Hulbert-Williams, Nicholas J; Jacobsen, Paul B; International Psycho-Oncology Society Research Committee
Summary The patient-reported depression measures that perform best in oncology settings have not yet been identified. We did a meta-review to integrate the findings of reviews of more than 50 depression measures used in adults with, or recovering from, any type of cancer. We searched Medline, PsycINFO, Embase, and grey literature from 1999 to 2014 to identify 19 reviews representing 372 primary studies. 11 reviews were rated as being of high quality (defined as meeting at least 20 criteria in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement). The Hospital Anxiety Depression Scale (HADS) was the most thoroughly evaluated measure, but was limited by cutpoint variability. The HADS had moderate screening utility indices and was least recommended in advanced cancer or palliative care. The Beck Depression Inventory was more generalisable across cancer types and disease stages, with good indices for screening and case finding. The Center for Epidemiologic Studies Depression Scale was the best-weighted measure in terms of responsiveness. This meta-review provides a comprehensive overview of the strengths and limitations of available depression measures. It can inform the choice of the best measure for specific settings and purposes.